2010
DOI: 10.1007/s10508-010-9693-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Erotic Thoughts, Attentional Focus, and Sexual Problems in a Community Sample

Abstract: According to Barlow's model of sexual dysfunction, anxiety in sexual situations leads to attentional focus on sexual performance at the expense of erotic cues, which compromises sexual arousal. This negative experience will enhance anxiety in future sexual situations, and non-erotic thoughts (NETs) relevant to performance will receive attentional priority. Previous research with student samples (Purdon & Holdaway, 2006; Purdon & Watson, 2010) has found that people experience many types of NETs in addition to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 46 publications
8
26
0
Order By: Relevance
“…Perhaps difficulties in functioning trigger non-erotic thoughts, which may compromise the success of the corrective strategy (e.g., in the case of trying to change thoughts) or lead the person to make changes that actually do not facilitate sexual functioning (e.g., monitoring and moving the partner's hand away from body areas of which one is self-conscious, rather than focusing on the partner's pleasure or other arousing aspects of the experience). This is certainly consistent with Nelson and Purdon (2011), who found that greater difficulty re-focusing on erotic aspects of the sexual experience after the occurrence of a non-erotic thought was associated with poorer sexual functioning.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Perhaps difficulties in functioning trigger non-erotic thoughts, which may compromise the success of the corrective strategy (e.g., in the case of trying to change thoughts) or lead the person to make changes that actually do not facilitate sexual functioning (e.g., monitoring and moving the partner's hand away from body areas of which one is self-conscious, rather than focusing on the partner's pleasure or other arousing aspects of the experience). This is certainly consistent with Nelson and Purdon (2011), who found that greater difficulty re-focusing on erotic aspects of the sexual experience after the occurrence of a non-erotic thought was associated with poorer sexual functioning.…”
Section: Discussionsupporting
confidence: 87%
“…The current study replicated the findings of Purdon and Holdaway (2006) and Nelson and Purdon (2011) with respect to the content of non-erotic thoughts. In all three studies, non-erotic thoughts fell readily into performance, body concerns, external consequences, and emotional consequences categories.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These findings suggest that there is a broad range of cognitive distractions during sexual activity that extends beyond body image and performance concerns. Similar findings regarding the range of non-erotic cognitive distractions were obtained in a communitysample;however,significantlyfewerindividuals in the community sample reported having no distractions during sexual activity than in an undergraduate sample (Nelson & Purdon, 2010).…”
Section: Introductionsupporting
confidence: 76%